ADAT UANG HANTARAN PERNIKAHAN SESUKU DAN TIDAK SESUKU PADA MASYARAKAT MELAYU PETALANGAN (Studi Komunitas di Kelurahan Rawang Empat Kecamatan Bandar Petalangan Kabupaten Pelalawan) - Rika Dianti; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT This research was conducted in Rawang Empat Village, Bandar Petalangan District, Pelalawan Regency. This study aims to find out about the custom of surrender, as well as the differences between same-ethnic and non-ethnic marriage customs and the procedure for determining delivery money at the marriage of the Petalangan Malay people. This study used a descriptive qualitative method with five subjects consisting of three key informants and two subjects. For data collection in this study, namely using observation, interviews and documentation. Petalangan is an indigenous Riau Malay tribe who lives in Pelalawan Regency. The existence of marriage customs in the midst of society cannot be separated from efforts to communicate values, norms or rules that have been agreed upon in traditional marriage ceremonies. The application of customary marriage law is very much needed in indigenous peoples. This aims to maintain the sanctity and continuity of marriage. The Petalangan Malay custom is a combination of the Minangkabau customary system, which is matrilineal, and the Malay customary system, which is patriarchal. Rawang Empat Urban Village, Bandar Petalangan District, Pelalawan Regency, in this case, is still one of those who adhere to the exogamy marriage system, which requires people to marry people outside their tribe and marrying people from their own tribe is prohibited or in customary terms it is known as same-tribal marriage. From the differences in same-tribe and non-ethnic marriages, there is a comparison of traditional delivery money in its implementation. Keywords: Customs, Petalangan, Surrender Custom, Marriage